The Origins of Late Philistine Decorated Ware: A Note. (June 2015) - Maeir, Aren M.; Shai, Itzhaq
Abstract : A decade ago, the authors, along with D. Ben-Shlomo, defined Late Philistine Decorated Ware (LPDW, formerly Ashdod Ware) as typical of Iron IIA Philistia and discussed its origins and distribution. We suggested that the decorative syntax of this unique group could be traced to Iron I decorated Philistine pottery. This assertion was recently challenged by Faust, who suggested that its origins should be traced to Phoenician influence. Two LPDW sherds from Tell es-Safi/Gath that are decorated with the iconic Iron I Philistine bird design support our initial concept that the roots of the LPDW are in Iron I Philistia.